INVESTIGATION OF TITANIUM ADDITION ON PHYSICAL AND MECHANICAL PROPERTIES OF POWDER INJECTION MOLDED 316L STAINLESS STEEL PARTS - MOHMAD @ FIKRI, FAEZ (IRC, 2016)

(untitled)
Recently, stainless steel alloys are widely used in various industries especially in medical. In medical implants, 316L stainless steel alloy is being used as a hip bone fixation due to their good in strength. However, recent studies on this alloy have detected some critical problems to community. This is due to the residual of stresses produced during machining process of this alloy and directly causing the cracks to occur within the material. Unfortunately, these cracks decrease the strength of the material and lead to corrosion to occur in human body. Therefore, the objective of this project is to develop 316L stainless steel with Titanium addition and to investigate their mechanical and physical properties. Titanium alloys are biocompatibility, corrosion resistance and have specific strength which is too good to use in medical implants. The fabrication of 316L stainless steel with Titanium addition is conducted through Powder Injection Molding (PIM) method.